2016
DOI: 10.1108/jcs-03-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

The “Supporting Kids, Avoiding Problems” (SKIP) study: relationships between school exclusion, psychopathology, development and attainment – a case control study

Abstract: Purpose – The purpose of this paper is to explore the association between children who are at risk of being or who have been excluded from school between the ages of 4 and 12 years and the role of psychopathology, development and attainment. Design/methodology/approach – A case-control approach was conducted. Cases were children who had been excluded from school compared to those who had no reported exclusions and normative data where po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Prospectively collected data at population level offer an opportunity to study temporal relationships between poor mental health and exclusion from school, but given that the latter is uncommon, sufficiently large data sets are rare. Several studies suggested a strong relationship between psychiatric disorder and exclusion from school (Bowman-Perrott et al, 2011;Ford et al, 2012;Paget et al, 2018;Parker et al, 2016Parker et al, , 2018Patton et al, 2014;Whear et al, 2013). Analyses of data from a nationally representative population sample suggested a bidirectional relationship between exclusion and poor mental health (Ford et al, 2018), indicating that effective intervention to support the learning and mental health of children who struggle with school could prevent both future mental disorders and exclusions (Beckett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Prospectively collected data at population level offer an opportunity to study temporal relationships between poor mental health and exclusion from school, but given that the latter is uncommon, sufficiently large data sets are rare. Several studies suggested a strong relationship between psychiatric disorder and exclusion from school (Bowman-Perrott et al, 2011;Ford et al, 2012;Paget et al, 2018;Parker et al, 2016Parker et al, , 2018Patton et al, 2014;Whear et al, 2013). Analyses of data from a nationally representative population sample suggested a bidirectional relationship between exclusion and poor mental health (Ford et al, 2018), indicating that effective intervention to support the learning and mental health of children who struggle with school could prevent both future mental disorders and exclusions (Beckett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As the Education Select Committee (2018) reported from interviews with pupils, extended periods of learning time are frequently spent in exclusion units without specialist intervention-valuable learning time which could be utilised to provide intensive, evidence-informed psychological and cognitive interventions to support inclusion and integration in mainstream learning environments (Ghafoori, 2000). This correlates with the recommendation for immediate and comprehensive assessment intervention for all pupils whose persistent and disruptive behaviour threatens their continuation in the mainstream (Parker et al, 2016) as a means of heading exclusion off at the pass and empowering teachers via the careful and explicit identification of needs. Tragically, poor mental health rather academic ability was identified by the study as the key determinant in whether a pupil struggles or flourishes with school (Parker et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
“…This correlates with the recommendation for immediate and comprehensive assessment intervention for all pupils whose persistent and disruptive behaviour threatens their continuation in the mainstream (Parker et al, 2016) as a means of heading exclusion off at the pass and empowering teachers via the careful and explicit identification of needs. Tragically, poor mental health rather academic ability was identified by the study as the key determinant in whether a pupil struggles or flourishes with school (Parker et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations